If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
(3*m)/6-(m/3)+1/4 = 7/12 // - 7/12
(3*m)/6-(m/3)+1/4-(7/12) = 0
(3*m)/6-(m/3)+1/4-7/12 = 0
1/6*m-1/3 = 0 // + 1/3
1/6*m = 1/3 // : 1/6
m = 1/3/1/6
m = 2
m = 2
| 3g-16g=7+2(-8g-3) | | 8-(4x-5)=41 | | 20/x=2/2 | | 5d^2-3d+d= | | -3(x+4)-2(2x+8)=80 | | 75x+9=91x | | -105=-5(4x+1) | | c+12=57 | | 100-3(7)=20+5x | | 2/3-11=4+X | | -(-15p-1)+24+2(5+5p)=0 | | =mx+b | | 1/3x^2+1/3x-4 | | 3t+1/2t=28 | | 8x+5+4= | | 5x/14-4=x/7+14 | | -56=-4(2n+4) | | -22+6+9/5y=6+8 | | 5(44n-4)=-60 | | 184-1.7x=93+0.9x | | 10+(-9)=b | | 3.0*1.5= | | 4x+3-3x=5(x-3) | | 2y=9/11 | | 2z(8z+3)=16z^2+6z-2 | | 8x+6=8x-1 | | -3x(x^2+4x-5)= | | 4x+3-3x=d(x-3) | | 5-3=45 | | -3(-4b+5)-12b=-36 | | 1/5X2x-10+4 | | 2z-6=-8 |